Interaction of dense shelf water cascading and open‐sea convection in the northwestern Mediterranean during winter 2012. Issue 7 (15th April 2013) - Durrieu de Madron, X.; Houpert, L.; Puig, P.; Sanchez‐Vidal, A.; Testor, P.; Bosse, A.; Estournel, C.; Somot, S.; Bourrin, F.; Bouin, M. N.; Beauverger, M.; Beguery, L.; et al.
Abstract: [1] The winter of 2012 experienced peculiar atmospheric conditions that triggered a massive formation of dense water on the continental shelf and in the deep basin of the Gulf of Lions. Multiplatforms observations enabled a synoptic view of dense water formation and spreading at basin scale. Five months after its formation, the dense water of coastal origin created a distinct bottom layer up to a few hundreds of meters thick over the central part of the NW Mediterranean basin, which was overlaid by a layer of newly formed deep water produced by open‐sea convection. These new observations highlight the role of intense episodes of both dense shelf water cascading and open‐sea convection to the progressive modification of the NW Mediterranean deep waters. Key Points: Evidence of interaction of dense shelf water cascading with open‐sea convection 2012 winter event connected with peculiar atmospheric circulation patterns Formation of the near‐bottom thermo‐haline anomalies in the NW Mediterranean